2021
DOI: 10.18203/2349-3933.ijam20212802
|View full text |Cite
|
Sign up to set email alerts
|

Study of thyroid profile in pre and post-menopausal women: a case control study

Abstract: Background:The prevalence and incidence of thyroid disorders is influenced primarily by sex and age are more common in women and in older adults. Thyroid disorders if left untreated will increase risk of cardiovascular diseases and osteoporosis. Hence, screening for thyroid dysfunction must be done as routine investigation in the women presenting with menopausal symptoms.Methods:This case control study includes 50 pre-menopausal women of age group 34-49 years and 50 post-menopausal women of age group 50-55 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…The study concluded that postmenopausal women should have their serum T3, T4, and TSH levels checked to prevent thyroid dysfunction. Thus, an association between thyroid disorders and postmenopausal women was discovered; however, menopausal symptoms were not examined in their study [ 19 ]. The limitations of the study mainly involved a small sample size which can be overcome in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that postmenopausal women should have their serum T3, T4, and TSH levels checked to prevent thyroid dysfunction. Thus, an association between thyroid disorders and postmenopausal women was discovered; however, menopausal symptoms were not examined in their study [ 19 ]. The limitations of the study mainly involved a small sample size which can be overcome in future studies.…”
Section: Discussionmentioning
confidence: 99%